INNOVATIVE METHODS IN TEACHING ENGLISH - Zubaydullayeva Gulbahor (ZAMONAVIY TILSHUNOSLIK ISTIQBOLLARI: MUAMMOLAR VA YUTUQLAR MAVZUSIDA XALQARO ILMIY AMALIY ANJUMAN, 2025)
Modern English language education prioritizes actively involving learners and cultivating their independent, critical, and creative language use. This article explores how innovative teaching approaches, such as collaborative tasks, technology-integrated learning, problem-based education, and combining language with other subjects, contribute to improving students’ language skills. These methods shift the emphasis from simply receiving information to actively using the language, encouraging students to analyze, think deeply, and communicate effectively. The article also highlights the essential teaching conditions for successfully implementing these approaches, including well-defined lesson plans, a supportive learning atmosphere, and constructive feedback. Analysis shows that these innovative strategies not only enhance language acquisition but also build learners’ confidence and communicative competence.